An Analysis of Pronunciation Errors Made by Medical Students at S&I Learning Centre - Ida Ayu Maharani; I Wayan Pastika; Ni Luh Ketut Mas Indrawati (RETORIKA: Jurnal Ilmu Bahasa, 2020)
This study discusses about pronunciation errors made by medical students at S&I Learning Centre. The study aims to describe the types of pronunciation errors found in students' utterances using descriptive qualitative method. The subject are medical students at S&I Learning, meanwhile the object of this exploration are students' utterances in English. The data was collected through audio recording and then those was analysed by using theory proposed by Corder by classifying errors into three types. The results show that the sorts of pronunciation errors created by medical student and 2) the cause of pronunciation errors produced by medical students. Students’ pronunciation errors are also classified into three types. Those are interference errors, intralingual errors, and developmental errors. In speaking, teacher and students had their effect to each other. The teacher has duties to assess and address the error of students by addressing the errors produced by learners permanently, particularly at the time when they drilled and practiced the correct pronunciation in speaking skill. In addition, students too should be more dynamic in surveying and correcting the pronunciation themselves. They have to create and improve their pronunciation capacity by appreciating the hypothetical about legitimate phonological. In accordance with this reason, it is necessary to apply an appropriate learning model to reduce pronunciation errors produced by students.